An analysis of Organizational Culture Dimensions in Economic Enterprise: Empirical Study on Sample of Leather Tanning enterprises in Algeria. - بن عودة مصطفى (Milev Journal of Research and Studies, 2019)
This study dealt with the issue of of organizational culture dimensions in Leather-tanning institutions in Algeria. The study was applied to a sample of (142) employees, out of a study population of (714) employees. The study used a questionnaire as a tool for gathering information and data. The questionnaire was distributed on various workers in different organizational levels in the leather tanning institutions (Top management, Middle management, Lower management, Typical functions). The study concluded to a set of results including the following: The high level of awareness of all the dimensions of organizational culture (customer orientation, consistency and coherence, results orientation, adaptability, team orientation) as we noticed high levels, except two dimensions (creativity and innovation encouraging, inclusion and cohesion) in which we noticed medium levels. There is agreement in the views and perceptions of workers in the leather tanning institutions in Algeria, about the realization of organizational culture dimensions, and in spite of the difference of (gender, educational level, duration of service, the nature of the job, geographical distribution, the nature of the institution), but they disagree about the perception of the dimensions of organizational culture by: age of employee, length of service, the nature of employment contracts that bind workers in their institutions.